Controlled Desquamation of Urinary Bladder Epithelium by Cationic Polymer Poly-L-Lysine - Erman, Andreja; Kos, Mojca Kerec (Current Aspects in Pharmaceutical Research and Development Vol. 7, 2022)
The aim of our study was to evaluate the experimental conditions under which the cationic polymer poly-L-lysine induces effective and safe desquamation of the urinary bladder epithelium, also called the urothelium. Induced desquamation of the urothelium is a frequently used approach in studies of urothelium regeneration and also to establish animal disease models. Chitosan has previously been shown to induce large-scale desquamation of urothelial cells. We have investigated the desquamation ability of another positively charged polymer poly-L-lysine. Its effect on the functional and structural integrity of the urothelium was studied in ex vivo and in vivo experiments. The results revealed that the effect of poly-L-lysine on the structure and function of the urothelium was mainly influenced by the concentration of the polymer, while the treatment time and the molecular weight of poly-L-lysine had little effect. Fifteen minutes exposure of the urothelium to 0.01% poly-L-lysine was found to be efficient and safe in ex vivo and in vivo experiments and resulted in intense cell desquamation, which was limited to the superficial cell layer only. Functional and structural regeneration of the urothelium occurred ex vivo within 2 to 3 hours after the induced injury by poly-L-lysine. Therefore, poly-L-lysine is a promising inducer of urothelial cells desquamation that has the potential to be used in the clinic for the treatment of urologic disorders.